Systematic review of cosmetic benefit of topical application of ferment filtrate - Shangyi Fu; David Garate; Andrea Francis; Benjamin Garcia; Danny Huynh; Ida Orengo (Surgical & Cosmetic Dermatology, 2023)
Ferment filtrate (FF), a by-product of nutrient-rich yeast, is believed to be used cosmetically in East Asia since the 1970s. We systematically reviewed the topical effects of ferment filtrate on skin health and determined limitations in the available studies. Recent literature has shown evidence in reducing the baseline fluctuation of pore size, roughness, hyperpigmentation, and redness. However, these studies are limited in efficacy due to their small sample size, their confounding variables, and their limited generalizability. Because of the increase of cosmetic products containing this ingredient, critical analysis of the available and future literature is necessary to prevent consumer misinformation.